Morning or Afternoon: Does It Make a Difference in Early Childhood Programs?. Issue 3 (2nd July 2020) - Banerjee, Rashida; Horn, Eva; Palmer, Susan
ABSTRACT: Young children are often enrolled in either AM (morning) or PM (afternoon) sessions in early childhood programs. However, little research is available on this routine practice. We used multilevel analysis to investigate if there are differences in the literacy, math, and social outcomes for children who participate in AM or PM sessions beyond those that can be explained by differences in child, family, teacher, and session characteristics. Five hundred and eighty-eight preschool children in 63 half-day sessions participated in this study in five U.S. states. Results indicate there were no patterns of significant effects between time of day and preschool children's academic and social outcomes. However, a number of child, family, teacher, and session-level variables (e.g., child's age, gender, disability and language status, parents' education level, and teachers' years of experience) moderated the effect of time of day on children's cognitive and social outcomes. The findings highlight the need to further investigate how we constitute half-day programs and how enrollment patterns are established and implemented in preschool classrooms. Thus, the study has methodical implications for future research, policy, and practice.